Pemberontakan Petani Banten Tahun 1888 dalam Kitab Manhaj Al-Istiqamah Fi Ad-Din Bi As-Salamah Karya Sayyid Utsman Bin Yahya - Putri, Syifana A’Wuru; Najmul Umam, M Mutfi (UNIVERSITAS SERAMBI MEKKAH, 2025)
The peasant rebellion in Banten occurred in 1888 criticized by Sayyid Utsman bin Yahya through his work entitled Manhaj al-Istiqa ̅mah fi ̅ ad-Di ̅n bi as-Sala ̅mah. This peasant rebellion was a social movement launched by religious leaders. The leaders echoed the ideology of jihad, a holy war movement to attack the power of the Dutch colonial government which was considered an infidel power, but according to Sayyid Utsman, this rebellion was not a jihad movement but a mistaken religious movement. This study aims to determine the views of Sayyid Utsman in his work entitled Manhaj al-Istiqa ̅mah fi ̅ ad-Di ̅n bi as-Sala ̅mah regarding the peasant rebellion in Banten in 1888 AD. The method used is the historical method, namely; heuristics, criticism, interpretation, and historiography using the study of the theory of jihad 'Abd al-Samad al-Falimbani through his work entitled Nasihat al-Muslimin wa Tadzkirat al-Mu'minin fii Fada'il al-Jihad fi Sabil Allah wa Karamat al-Mujahidin fii Sabil Allah. This method was chosen to trace the life of Sayyid Utsman and the Banten peasant rebellion from a historical perspective. In this study the author found several results that had been traced, namely; regarding the manuscript of Sayyid Utsman Manhaj al-Istiqa ̅mah fi ̅ ad-Di ̅n bi as-Sala ̅mah which condemned the rebellion in Cilegon Banten as a wrong movement, and discussed a lot about heresy that was still carried out by the Nusantara community and followers of the tarekat. Sayyid Utsman was a scholar of fiqh, his works which were considered pro-Dutch became polemic. In addition, Sayyid Utsman's closeness to the Dutch made Sayyid Utsman receive many awards.